Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae) - Curletti, Gianfranco; Dutto, Angelo (Zootaxa, 2017)
A brief trip to Caquetà and Putumayo prov., South Colombia, during the month of November 2016, allowed us to discover two species new to science. The research was undertaken under the auspices of a joint educational/scientific project with the Apostolic Vicariate of the Consolata Fathers in the department of Putumayo (South Colombia).